2020
DOI: 10.7759/cureus.10520
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Morphologic Features of Lupus Nephritis According to Nephrology/Renal Pathology Society (ISN/RPS) Classification

Abstract: Introduction Lupus nephritis is one of the most important secondary glomerulopathy and a significant cause of chronic renal failure. Early diagnosis is key to improved prognosis. The International Society of Nephrology/Renal Pathology Society (ISN/RPS) classification stratifies renal biopsy evaluation in different classes that correlates with clinical renal outcome. In the current study, we aimed to evaluate the proportion of patients in each class of lupus nephritis in our population. Methods We evaluated ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
1
1
1
Order By: Relevance
“…In our study, we found that majority of patients were female, 50 (86.20%). The male-to-female ratio was 1:6.5 in our study, which is similar to other studies on LN, such as the studies by Hashmi et al and Farah et al [ 5 , 9 ]. C3 and C4 levels were decreased in 50 (86.20%) and 51 (87.90%) patients, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, we found that majority of patients were female, 50 (86.20%). The male-to-female ratio was 1:6.5 in our study, which is similar to other studies on LN, such as the studies by Hashmi et al and Farah et al [ 5 , 9 ]. C3 and C4 levels were decreased in 50 (86.20%) and 51 (87.90%) patients, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…We present a study in which the highest frequency was found of class V LN, 25 (43.10%), followed by class IV, 16 (27.58%), which is different from that seen in different studies conducted worldwide and in Pakistan in which the highest prevalence of class IV followed by class V was noted [ 5 , 9 ]. The more frequent prevalence of class V in our study may be due to the fact that we receive renal biopsies from all over Pakistan including the backward regions of our country where patients most of the time present at advanced stages because of lack of access to health care and poor infrastructure.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation